The Diagnostic Value of Onconeural Antibodies Depends on How They Are Tested - Ruiz-García, Raquel; Martínez-Hernández, Eugenia; Saiz, Albert; Dalmau, Josep; Graus, Francesc (Frontiers in Immunology, 2020)
Detection of onconeural antibodies is important because establishes a definitive diagnosis of paraneoplastic neurological syndrome (PNS). The recommended method for diagnosis of onconeural antibodies is by immunohistochemistry on rodent brain sections and confirmation of results by immunoblot. However, in many diagnostic laboratories samples are only tested with commercial line blots. In this study we inquired whether this change in diagnostic methodology (line blot alone vs. combined immunohistochemistry and line blot) would affect the results. Among 439 samples examined by immunohistochemistry and a commercial line blot (Euroimmun, Lübeck, Germany) 96 (22%) were positive by line blot, and their clinical information was reviewed. Onconeural antibodies were detected by both assays in 46/96 (48%) patients (concordant group) whereas 50 (52%) were only positive by line blot (discordant group). In the concordant group 42/46 (91%) patients had a definite diagnosis of PNS whereas in the discordant group only 4/50 (8%) had PNS (p < 0.00001). None of the 14 patients with ZIC4 antibodies and 1/13 (8%) with Yo antibodies demonstrated only by line blot had PNS. These findings show a robust diagnostic value of combined diagnostic techniques, and both should be used to demonstrate onconeural antibodies, If antibody testing is performed only with line blot assay, positive bands should be confirmed by rodent brain immunohistochemistry. For ZIC4 or Yo antibody testing, line blot positivity with negative immunohistochemistry has no diagnostic significance, and for the rest of onconeural antibodies the predictive diagnostic value is low.